We sang you home = Ka kîweh nikâmôstamâtinân - Van Camp, Richard 1971- (Orca Book Publishers, 2018)
This dual-language book celebrates and welcomes baby into the world
"This translation in the Plains Cree 'Y' dialect using Standard Roman Orthography was provided by Mary Cardinal Collins"--Colophon
Place of publication taken from publisher's website
Originally published as an English-only board book in 2016
Keywords: Zeremonie; Säugling; Gesang; Plains Cree; Familie; Kanada; Infants / Juvenile fiction; Families / Juvenile fiction; Board books; Cree language materials / Bilingual; Children's poetry, Canadian (English); Livres tout carton; Families; Infants; Fiction; Juvenile works; Poetry; Poésie; Bilderbuch